A Preliminary Investigation on the "Swinging Kidney": A Sonographic Sign Useful for Diagnosing Renal Colic. (July 2022) - Castelletto, Silvia; Amore, Giulia; Giudice, Caterina Anna; Orso, Daniele; Copetti, Roberto
Objective: During acute renal colic due to nephrolithiasis, a new sonographic diagnostic sign was noted, called "a swinging kidney." This term was given due to a characteristic anteroposterior "rolling" movement of the kidney. A preliminary investigation was conducted to evaluate the correlation between this new diagnostic sign and nephrolithiasis. Materials and Methods: An exploratory observational investigation was conducted on adult patients who accessed an emergency medicine department, with acute renal colic, between June 1, 2019, and October 31, 2019. Results: Thirty-seven patients were enrolled. The "swinging kidney" was present in 26 cases (70%). This sign was correlated with a stone's diameter of less than 10 mm (χ 2 : 4.68; P = .031), and with a stone localization in the juxtavesical ureter tract site (χ 2 : 10.83; P = .029). Spontaneously stone expulsion was correlated with the presence of the "swinging kidney" (χ 2 : 4.66; P = .031); with the minor degree of hydronephrosis (χ 2 : 16.82; P = .0008), and with a distal localization of the stone (χ 2 : 25.11; P = 1:47 × 10 −5 ). Conclusion: The "swinging kidney" may be a promising diagnostic sign that could be useful in diagnosing nephrolithiasis besides the other indirect sonographic signs. This new diagnostic sign could have a prognostic role.